Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1954
DOI: 10.1099/00221287-10-1-68
|View full text |Cite
|
Sign up to set email alerts
|

A New Type of Polar Monotrichous Flagellation

Abstract: SUMMARY : An organism with a new type of polar monotrichous flagella is described. The flagella have a very short wavelength which is very characteristic. The organism liquefies gelatin and oxidizes ethanol to acid. All other common differential tests were negative. The name Pseudornonas diminuta n.sp. is suggested.The curvature of bacterial flagella is quite constant and sufficiently characteristic to be of considerable taxonomic importance. The usual wavelength of the flagella of such polar monotrichous bact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Year Published

1954
1954
2016
2016

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 2 publications
0
19
0
Order By: Relevance
“…diminuta. This latter appears a striking difference, but the present writer feels that the creation of this new species of Pseudomonas by Leifson & Hugh (1954) on the sole basis of the unusual flagella wavelength may be questioned. Indeed the allocation of Leifson & Hugh's organism to the genus Pseudomonas may be queried because of lack of pigment, no acid production from glucose, rapid production of acid (which acid?)…”
Section: E Rhodesmentioning
confidence: 79%
“…diminuta. This latter appears a striking difference, but the present writer feels that the creation of this new species of Pseudomonas by Leifson & Hugh (1954) on the sole basis of the unusual flagella wavelength may be questioned. Indeed the allocation of Leifson & Hugh's organism to the genus Pseudomonas may be queried because of lack of pigment, no acid production from glucose, rapid production of acid (which acid?)…”
Section: E Rhodesmentioning
confidence: 79%
“…Pseudomonas diminuta was originally defined by its unusual flagellar structure. This organism is monotrichous, and the flagellum is very small and tightly coiled (27). Investigations of Pseudomonas diminirta and Pseiidomonas vesicularis strains showed that these organisms utilize a quite limited range of carbon sources and require pantothenate, biotin, and cyanocobalamin as growth factors (2).…”
Section: Discussionmentioning
confidence: 99%
“…The temperature employed for growth was 30 OC and Pseudomonas Isolation Agar (Difco) was Leifson & Hugh (1954) NCIB 1054:l Strain CH-50 Palleroni et al (1970) replaced by medium A for growth of strains NCIB 10541, NCIB 9040, NCIB 9946, NCIB 8893 and NCIB 9393.…”
Section: E T H O D Smentioning
confidence: 99%